Effect of Matricaria aurea (Loefl.) Shultz-Bip. Hydroalcoholic Extract on Acetic Acid-Induced Acute Colitis in Rats - Mohsen Minaiyan; Nasrollah ghassemi-Dehkordi; Parvin Mahzouni; Meysam Ansari-Roknabady (Iranian Journal of Basic Medical Sciences)
Objective(s) Matricaria aurea is found abundant in Iran and has large similarities in constituents especially essential oils, flavones and flavonoides as well as traditional uses to the main species; Matricaria recutita L. Anti-inflammatory, antioxidant and spasmolytic properties of the main species suggest that this plant may have beneficial effects on inflammatory bowel diseases so the present study was carried out.Materials and MethodsHydroalcoholic extract of plant with doses of 200, 400, 800 mg/kg were administered orally (p.o.) for 5 days and rectally (i.r.) (400 and 800 mg/kg) at 15 and 2 hr before ulcer induction. To induce colitis, 2 ml of acetic acid 4% was instilled intra-colonically to separate groups of male Wistar rats (n= 6). Normal saline (2 ml), prednisolone (4 mg/kg) and hydrocortisone acetate (20 mg/kg) enema were administered to control and reference groups respectively. The tissue injures were assessed macroscopically and histopathologically. ResultsGreater doses of extract (400 and 800 mg/kg) reduced colon weight/length ratio (P< 0.01) and the highest test dose (800 mg/kg p.o. or i.r.) was effective to decrease tissue damage parameters including ulcer severity, area and index (P< 0.01) as well as inflammation severity and extent, crypt damage and total colitis index (P< 0.01) significantly. ConclusionIt is concluded that Matricaria aurea extract was effective to protect against acute colitis in acetic acid model and this effect was more significant with the greater doses administered orally or rectally. Further studies are warranted to ascertain the mechanisms that are involved and the responsible active constituents.